(untitled) - Hajek, Ann E. (Cambridge, UK, 2004)
The book gives a thorough grounding in the biological control of arthropods, vertebrates, weeds, and plant pathogens through use of natural enemies. The book is intended for undergraduate students and others wishing to learn the basics of biological control. Ann Hajek discusses the reasons why biological control is used, and describes different use strategies and associated safety issues, as well as how best to integrate biological control with other types of pest management. She goes on to describe the basic biology of the different types of natural enemies, and gives examples of successful biological control programs. Throughout this book the ecological relationships that make control possible are emphasized and the major strategies for the use of different types of natural enemies detailed, with discussions of the specific conditions under which each strategy is successful in controlling pests (Editorial Reviews)
Keywords: Pests,Weeds,Sâu hại,Cỏ dại; Biological control,Biological control,Kiểm soát sinh học,Kiểm soát sinh học